Методологія дослідження стану впровадження цифрових інструментів зовнішнього та внутрішнього маркетингу в сільськогосподарських кооперативах - Безус, Роман Миколайович; Bezus, Roman; Крючко, Леся Станіславівна; Kriuchko, Lesia (Херсонський державний університет, 2022)
У статті з огляду на світовий досвід розглянуто та обґрунтовано, що одним із дієвих механізмів підвищення ефективності маркетингової діяльності дрібних, малих і середніх виробників виступають створення та функціонування сільськогосподарських кооперативів. Систематизовано найбільш популярні сьогодні інструменти зовнішнього маркетингу. Зазначено, що найбільшого значення набувають нині використання мобільних додатків, створення сайтів та просування продукції через Інтернет-майданчики вільного продажу товарів. Дослідниками на основі використання даних Держстату України узагальнено інформацію щодо кількості підприємств та використання ними інформаційно-комунікаційних технологій. Зазначено, що інформація щодо стану впровадження інформаційно-комунікаційних технологій на сільськогосподарських підприємствах України в офіційних статистичних джерелах відсутня. У зв’язку із цим авторами запропоновано внести зміни у нормативні акти для можливості отримання невеликими сільськогосподарськими підприємствами маркетингових переваг та якісного поліпшення зовнішнього та внутрішнього маркетингу створених сільськогосподарських кооперативів. The article considers and substantiates the world experience that one of the effective mechanisms of increasing efficiency of marketing activity of micro, small and medium producers is the creation and functioning of agricultural cooperatives. It is characterized that in relation to agricultural cooperatives distinguish internal and external marketing and disclosed their essence with the point of view of the authors that these types of marketing should be implemented in a complex and each of them applies a certain set of tools, including digital. The most popular tools of external marketing for today are systematized. The authors have indicated the opinion that from the given digital tools of marketing in the activity of agricultural enterprises it is expedient to use the majority of them simultaneously with their differentiation under concrete needs and purposes. The authors noted that the greatest importance is now acquired by the use of mobile applications, the creation of websites and product promotion through online platforms for the free sale of goods. Researchers, based on data from the State Statistics Service of Ukraine, summarized information on the number of enterprises and their use of information and communication technologies. It was noted that there is no information about the state of implementation of information and communication technologies in agricultural enterprises in official statistical sources. The authors of the article analyzed the information from the site "Ukraine Today: Directory of leading enterprises of Ukraine" in terms of agro-industrial and food companies in Ukraine on the availability of agricultural and processing of agricultural products websites. The analysis showed that microenterprises marketing tools and digital, in particular, are not used, that is, they do not even have a website; small businesses that have a website, about 5% of their total number; among medium-sized companies website is about 80% of companies. In this regard, the authors proposed to amend the regulations to enable small agricultural enterprises to obtain marketing advantages and qualitatively improve the external and internal marketing of established agricultural cooperatives.
Methodology for the study of the state of implementation of digital tools of external and internal marketing in agricultural cooperatives
Keywords: сільськогосподарські кооперативи; agricultural cooperatives; цифрові інструменти; digital tools; інформаційно-комунікаційні технології; information and communication technologies; маркетингові переваги сільськогосподарських підприємств; marketing advantages of agricultural enterprises